VASOGENIC EDEMA AND HYDROCEPHALUS AS COMPLICATIONS OF GLIOBLASTOMA - Ari Bandana Tasrif (PT. Radja Intercontinental Publishing, 2025)
Glioblastoma is the most aggressive and common primary brain tumor in adults, characterized by rapid growth, infiltrative behavior, and poor prognosis despite multimodal treatment. Among its most significant complications are vasogenic edema and hydrocephalus, which exacerbate intracranial hypertension and contribute substantially to morbidity and mortality. We report the case of a 59-year-old male who presented with progressive decreased consciousness, severe headaches, right-sided weakness, and visual disturbances. Neuroimaging revealed a left temporoparietal mass with cystic, solid, and necrotic components, accompanied by extensive vasogenic edema, midline shift, and obstructive hydrocephalus. Histopathological examination confirmed glioblastoma, WHO grade IV. The patient was treated with intravenous dexamethasone and acetazolamide, resulting in improved consciousness and partial symptomatic relief. This case illustrates the pathophysiological role of blood–brain barrier disruption in vasogenic edema and cerebrospinal fluid flow obstruction in hydrocephalus. Dexamethasone remains the cornerstone of symptomatic management for edema, while acetazolamide may provide temporary benefit in hydrocephalus, although its long-term efficacy is limited. The coexistence of these complications significantly worsens prognosis, and treatment primarily focuses on symptom control and quality of life. Prompt recognition and appropriate management are essential to stabilize patients, even though overall survival in glioblastoma remains limited.